Attribute Destinasi Halal Dan Pengaruhnya Terhadap Nilai Yang Dirasakan Pada Daerah Destinasi Wisata Halal Kota Padang - Haryeni; Nofri Yendra (GLOBAL SCIENTS PUBLISHER, 2025)
The purpose of this study was to determine the influence of halal tourism destination attributes on perceived value. The population in this study were local tourists visiting halal tourism destinations in West Sumatra, namely Padang City. A series of exploratory and confirmatory analysis factors were used to assess the research constructs, validity, and reliability of the composite. The sample size of this study was 150 respondents. The data analysis technique used in testing the research hypothesis was the Partial Least Square (PLS) program. Based on the results of the study, halal tourism destination attributes have a significant effect on perceived value.